Caracterização multi-escalar de bandas de deformação nas tectonossequências paleozóica, pré- e sin-rifte da Bacia do Araripe, Nordeste do Brasil - Netto, João Marculino de Araújo (2011)
Deformation bands are structures, developed in porous sandstones, that has small offsets and they are not shown on seismic section. The deformation bands of the pre and synrift sandstones of Araripe Basin were studied in outcrop, macroscopic and microscopic scales. The hierarchical, cinematic and spatial-geometric characteristics, and also the deformational mechanisms acting during its structural evolution were established too. In general, the mesoscopic scale observation allowed to discriminate deformation bands as singles or clusters in three main sets: NNE-SSW dextral; NE-SW normal (sometimes with strike-slip offset); and E-W sinistral; further a bed-parallel deformation bands as a local set. The microscopic characterization allowed to recognize the shearing and cataclastic character of such structures. Through the multi-scale study done in this work we verified that deformation bands analyzed were preferentially developed when sandstones under advanced stage of lithification. We also infer that the geometrical-spatial complexity of these bands, together with the presence of cataclastic matrix, can difficult the migration of fluids in reservoir rocks, resulting on their compartmentalization. Therefore, the study of deformation bands can aid researches about the structural evolution of sedimentary basin, as well as collaborate to understand the hydrodynamic behavior of reservoirs compartmented by these deformational structures